2022
DOI: 10.18388/abp.2020_6027
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-655-3p inhibits growth, and invasion and macrophage M2 polarization through targeting CXCR4 in papillary thyroid carcinoma

Abstract: Papillary thyroid cancer (PTC) is an endocrine malignancy whose incidence has increased rapidly worldwide. Exosome-miR-655-3p was down-regulated in patients with PTC. However, the effect and molecular mechanism of exosome-miR-655-3p in PTC was indistinct until now. Our study found that exosome-miR-655-3p was decreased in serum of PTC patients. Overexpression of miR-655-3p with mimics significantly shrunk the cell viability, reduced the number of chemotactic and invasive PTC cells. Besides, the proportion of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other pathways involved in macrophage recruitment include CXCL12-CXCR4 and angiopoietin 2 (ANG2)–TIE2 axis ( 57 59 ). Therefore, depletion of TEM could cause vascular destruction, neutralization of ANG2 can improve the response to vascular VEGFA blockade, and inhibition of TEM recruitment can inhibit tumor growth ( 60 ).…”
Section: Targeting Macrophages In the Tumor Microenvironmentmentioning
confidence: 99%
“…Other pathways involved in macrophage recruitment include CXCL12-CXCR4 and angiopoietin 2 (ANG2)–TIE2 axis ( 57 59 ). Therefore, depletion of TEM could cause vascular destruction, neutralization of ANG2 can improve the response to vascular VEGFA blockade, and inhibition of TEM recruitment can inhibit tumor growth ( 60 ).…”
Section: Targeting Macrophages In the Tumor Microenvironmentmentioning
confidence: 99%
“…Exosomes miR-655-3p inhibits growth, invasion, and macrophage M2 polarization in papillary thyroid carcinoma by targeting CXCR4. The results indicated that the regulation of exosomes miR-655-3p/CXCR4 may be a potential therapeutic strategy for PTC ( 162 ). Some scholars have also conducted corresponding research on the relationship between extracellular miRNAs and drug resistance.…”
Section: Therapeutic Role Of Macrophage Polarization Induced By Mirna...mentioning
confidence: 97%
“…Papillary thyroid cancer (PTC) is an endocrine malignancy, and the role and molecular mechanism of miR-655-3p in PTC are currently unclear. A study conducted by Qiao et al ( 162 ) revealed that overexpression of miR-655-3p with mimics significantly reduced tumor cell viability, chemotaxis and invasiveness. Exosomes miR-655-3p inhibits growth, invasion, and macrophage M2 polarization in papillary thyroid carcinoma by targeting CXCR4.…”
Section: Therapeutic Role Of Macrophage Polarization Induced By Mirna...mentioning
confidence: 99%